2014
DOI: 10.1038/nmeth.3177
|View full text |Cite
|
Sign up to set email alerts
|

LysargiNase mirrors trypsin for protein C-terminal and methylation-site identification

Abstract: To improve proteome coverage and protein C-terminal identification, we characterized the Methanosarcina acetivorans thermophilic proteinase LysargiNase, which cleaves before lysine and arginine up to 55 °C. Unlike trypsin, LysargiNase-generated peptides had N-terminal lysine or arginine residues and fragmented with b ion-dominated spectra. This improved protein C terminal-peptide identification and several arginine-rich phosphosite assignments. Notably, cleavage also occurred at methylated or dimethylated lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
207
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(220 citation statements)
references
References 39 publications
12
207
0
1
Order By: Relevance
“…We were able to confirm this result utilizing the recently described LysargiNase Archaea protease. This cleaves N-terminally to lysine and arginine and, importantly, allows the abundance of methylated and unmethylated peptides to be compared as it cuts effectively at methyl-lysines and -arginines (27). With LysargiNase, we observed a complete loss of mono-, di-, and trimethylation of Lys 79 upon knockout of EFM5 (Supplemental Fig.…”
Section: Methyltransferases That Act On Lysine 79 In Eef1a Arementioning
confidence: 91%
“…We were able to confirm this result utilizing the recently described LysargiNase Archaea protease. This cleaves N-terminally to lysine and arginine and, importantly, allows the abundance of methylated and unmethylated peptides to be compared as it cuts effectively at methyl-lysines and -arginines (27). With LysargiNase, we observed a complete loss of mono-, di-, and trimethylation of Lys 79 upon knockout of EFM5 (Supplemental Fig.…”
Section: Methyltransferases That Act On Lysine 79 In Eef1a Arementioning
confidence: 91%
“…Such analyses will be facilitated by our recent introduction of a new protease for proteomics sample preparation, LysargiNase, which mirrors trypsin selectivity and hence generates C-terminal peptides with a positive arginine or lysine residue at their N-terminus, thus greatly improving detection and identification of protein C-terminal peptides (see section 2.3 for more details). 50 With the advent of LysargiNase for shotgun analyses and positional proteomics techniques, such as C-TAILS (Carboxy-Terminal Amine-based Isotope Labeling of Substrates), 39 to enrich for protein C-termini, it is anticipated that the focus and understanding of protein C-termini will greatly increase in the near future.…”
Section: C-terminal Modificationsmentioning
confidence: 99%
“…LysargiNase [69]. Alignment of the CD sequence of mirolysin with five members of family M43B belonging to the three kingdoms of life revealed that mirolysin possesses both an Figure 4A; [68,70]).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the ionic strength of buffers at pH 7.5 is 0.027 for HEPES, 0.035 for MOPS, and 0.042 for Tris, which correlates with the observed differences in activity. Determination of mirolysin specificity: As mentioned previously, the name of the archaeal metalloprotease ulilysin was changed to LysargiNase in order to better describe the specificity of the enzyme, which is restricted to Xaa-Lys and Xaa-Arg peptide bonds [69]. To determine whether mirolysin shows the same specificity, mMir was incubated with the following proteinaceous substrates: bovine casein and human albumin, fibrinogen, fibronectin, complement proteins (factors C3, C4, and C5), and the peptides human cathelicidin LL-37 and bovine insulin β-chain.…”
Section: Purification Of Mature Mirolysinmentioning
confidence: 99%
See 1 more Smart Citation